PENGEMBANGAN GULA CAIR BERBAHAN BAKU UBI KAYU SEBAGAI ALTERNATIF GULA KRISTAL DENGAN PENDEKATAN SISTEM INOVASI - Suripto Suripto; M. Syamsul Maarif; Yandra Arkeman (JURNAL TEKNIK INDUSTRI, 2013)
Alternative sweetener (glucose and fructose syrup) made from cassava is still imported.Potential of domestic raw materials is very large. In terms of technology and businessfeasibility, commercialization of small-scale manufacturing of liquid sugar can be done. Thisproduct is also excellent for food, beverages and medicines. The problem is the innovationprocess is not so well known in the wider community. As an alternative strategic food product,the development of this product is the responsibility of the government. The purpose of thispaper is to study the development of liquid sugar made from raw cassava with the innovationsystems approach. Innovation system which is used in this assessment is the system ofagricultural innovation by Termel, et al in Zuhal (2010). Key to the success of this developmentis the process of diffusion of innovations to investors in the centers of production and diffusionof cassava products to the public. The method used is coaching and training, campaigns andsocialization benefits products.